Identify Obstacles of Different Types in the Path of UGV Using Region Based Image Segmentation (International Journal of Engineering and Computer Science, 2015)
— Unmanned ground vehicle is a smart autonomous vehicle that is mainly capable to do tasks without the need of humanoperator. An automated vehicle work during off road navigation and mainly used in military operation such as detecting bombs, borderpatroling.These types of automated vehicles are required even in driving road vehicles where human errors cause major fatal loss of lifeand property. For this purpose the functionality of unmanned ground vehicle can be enhanced by using region based imagesegmentation which will help to identify the obstacles that come in the path of UGV.In this paper, Region based image segmentationalgorithm is proposed to identify obstacles (car, human, tree etc).This method is compared with edge based image segmentation methodbased on three parameters (angle of projection, angle of disjunction and angle of disjunction). Based on comparisons, region basedimage segmentation algorithm is capable of producing more accurate results as compared to edge based segmentation algorithm.